APPLYING REALIA TO IMPROVE STUDENTS’ WRITING ON A DESCRIPTIVE TEXT - Rosdiana (English Education Department, 2016)
In learning process, a teacher is required to be able to select the appropriate method for teaching students to write text. One of the texts that should be learned by students is descriptive text. The purpose of this research is to improve students' writing descriptive text. It is an experimental study that employed One – Group Pretest-Posttest Design in which there was one class as an experimental class which was taught using Realia. The subject of this study conducted in class VII at SMPN 18 Banda Aceh. There were 21 students taken as sample of this research. Technique of data collection in this research is using test. While to analyze the data, the writer used quantitative analysis by using some statistical formulas. After the writer applied the media, the writer looked at a positive improvement on the students’ writing. It was turned out that this media really help students in writing descriptive text. The result of data analysis demonstrated that there was a significant difference on students’ achievement from both tests proved by average of the pre-test and post-test’s score. As a result, the post-test’s mean score (84, 07) is higher than pre-test’s mean score (60, 7), which the score of t-test was 18,45 and the value for t-table was 2,08 at a level of significance 0,05. It can be concluded that the students who were taught by using realia had a better performance in learning writing especially on descriptive text. In brief, realia enables to increase the students’ achievement in learning writing and it gave a positive effect on writing teaching and learning process. It helps students’ in writing a descriptive text by looking directly the object that they would describe.